2004
DOI: 10.1159/000076720
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Association Study between the Monoamine Oxidase A Gene and Obesity: Implications for Psychopharmacogenetic Studies

Abstract: Family studies have reported that obesity has a strong heritable component. It has been suggested that a neurotransmitter dysfunction could be involved in mental disorders and obesity; therefore, candidate genes in psychiatric disorders could be a risk factor for obesity. We investigated the association between the monoamine oxidase A (MAO-A) gene and obesity. Fifty obese subjects and their parents were included in the study. Two polymorphisms designated EcoRV and upstream variable number tandem repeats of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
(19 reference statements)
2
20
0
1
Order By: Relevance
“…In a large U.K. cohort (n=1,150) of Caucasian females, significant associations were detected between MAOA and Body Mass Index (BMI), with the low-activity u-VNTR genotype (3/3) being more frequent among obese females (Need, Ahmadi, Spector, & Goldstein, 2006). This finding supports a previous family-based study in which preferential transmission of the low activity allele was observed among subjects with BMI >= 35 kg/m 2 (Camarena et al, 2004). Also, the association between the low activity allele and obesity was observed among white and Hispanic, but not African-American, men in a U.S. cohort of young adolescents and adults (Fuemmeler et al, 2008).…”
Section: Introductionsupporting
confidence: 92%
“…In a large U.K. cohort (n=1,150) of Caucasian females, significant associations were detected between MAOA and Body Mass Index (BMI), with the low-activity u-VNTR genotype (3/3) being more frequent among obese females (Need, Ahmadi, Spector, & Goldstein, 2006). This finding supports a previous family-based study in which preferential transmission of the low activity allele was observed among subjects with BMI >= 35 kg/m 2 (Camarena et al, 2004). Also, the association between the low activity allele and obesity was observed among white and Hispanic, but not African-American, men in a U.S. cohort of young adolescents and adults (Fuemmeler et al, 2008).…”
Section: Introductionsupporting
confidence: 92%
“…39 In a recent linkage study on anorexia nervosa, high-activity alleles were found to be mildly overtransmitted in patients with low BMI, 50 while in another study low MAOA enzyme activity was associated with severe obesity (BMIX35 kg/m 2 ). 38 To our knowledge, our study is the first to report an effect of the MAOA-LPR locus on BMI in a population of mainly nonobese individuals. Although this association is intriguing, it is preliminary and in need of further investigation before any firm conclusions should be drawn.…”
Section: Discussionmentioning
confidence: 66%
“…36 The possible involvement of MAOA in obesity is supported by a whole genome linkage study implicating a locus for obesity on the p arm of the X chromosome, 37 as well as a study in which low activity MAOA alleles were associated with obesity in one familial data set. 38 Finally, MAOA inhibitors, at least the irreversible types, typically cause weight gain. 39 The goal of the present study is to test the hypothesis that heritable variation in MAOA-LPR contributes to interindividual differences in (1) CSF levels of monoamine metabolites; (2) the risk of developing alcoholism and other related externalizing phenotypes such as ASPD, borderline personality disorder (BPD), intermittent explosive disorder (IED), and high novelty seeking (NS); and (3) body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…It and its partner MAOB are located in the mitochondria of neurons and break down dopamine that has already been removed from the synaptic cleft. A 30-base-pair VNTR of the MAOA isoform of this gene is in the promoter region (Camarena et al, 2004). The promoter region of a gene is where the initial binding of transcription proteins takes place, so polymorphisms in this area are particularly influential on gene product availability.…”
Section: Genetic Evidence For the Relationship Between Obesity And Thmentioning
confidence: 99%
“…Individuals with the 3.5- and 4-repeat alleles show greater mRNA production than those with the other alleles (Sabol et al, 1998), and boys with the longer repeats have a greater preference for high-fat and sugary foods than those with shorter repeats (Galvao et al, 2012). Additionally, shorter alleles are in transmission disequilibrium in obese families (Camarena et al, 2004). …”
Section: Genetic Evidence For the Relationship Between Obesity And Thmentioning
confidence: 99%